Prevention and protection measures of healthcare workers exposed to SARS-CoV-2 in a university hospital in Bari, Apulia, Southern Italy. Issue 3 (July 2020) - Vimercati, L.; Dell'Erba, A.; Migliore, G.; De Maria, L.; Caputi, A.; Quarato, M.; Stefanizzi, P.; Cavone, D.; Ferorelli, D.; Sponselli, S.; Mansi, F.; Tafuri, S.
SUMMARY: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-related infection has a major impact on public health, and healthcare workers (HCWs) are exposed to high biological risk. This paper describes the prevention procedures introduced at the University Hospital of Bari, Italy to reduce the risk to HCWs, consisting of enhanced preventive measures and activation of a report system to collect HCWs' contacts. Twenty-three confirmed cases of infection (0.4% of all HCWs) were reported in the 30-day observation period following implementation of the protocol. This shows that correct management of HCWs' contacts is essential to avoid nosocomial clusters.